RELEVANSI IDENTITAS AGAMA DI TENGAH DOMINASI IDENTITAS NEGARA-BANGSA - Miftah Farid Darussalam; Mirah Satria Alamsyah (Indonesian Journal of International Relations, 2022)
This writing argues that nation-states could be treated as an identity rather than only the accepted actor of international relations. Understand nation-states as an identity is important, following the constructivist argument that identity could shape an individual or even nation-states' intention. Nation-states as the main actor of international relations impacted to their intention define only by the identity that emerges from it. Although, other identities especially religious identity in this writing argued still relevant in the identity conceptual framework that this paper provides. This paper highlights that nation-states identity work as representative identity, as the basis of identification over self-image on the surface. Meanwhile, religious identity lies within the nation-states; it might not always represent nation-states but could do so on a contextual basis. This is qualitative research using identity as the conceptual framework. Then, literature studies as the method and data collection been done by collecting relevant academic journals, books, and other relevant articles.